KEBERLANJUTAN KARIR GURU DI ERA SMART SCHOOL: TANTANGAN KESEJAHTERAAN DAN RESPONS ORGANISASI - Nurajizah; Eka Setiahati; Fuad Abdul Baqi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The Smart School era demands teachers to adapt to complex digital ecosystems, yet these requirements often overlook the essential aspect of educator well-being, which is vital for career sustainability. This article aims to explore the challenges to teacher well-being and the role of organizational responses in mitigating risks within the digital era. Utilizing a narrative literature review method, this study analyzes various scientific sources concerning technostress, digital burnout, and human resource management in educational institutions. The review findings indicate that technology integration, when not accompanied by adequate organizational support, triggers emotional exhaustion and diminishes teachers' intention to remain in the profession. It was found that teachers' occupational well-being is significantly influenced by school structures, digital workloads, and technology-related self-efficacy. In conclusion, organizational responses through empathetic digital leadership, continuous professional training, and policies that safeguard work-life balance are imperative to ensure teacher career sustainability in the future. Keywords: Smart School, Teacher Well-being, Technostress, Organizational Response, Career Sustainability.